Pengaruh Iklan Televisi Dan Desain Kemasan Terhadap Keputusan Pembelian Sabun Pembersih Wajah Biore pada Mahasiswa Universitas Negeri Padang - Rezki Nofriyanto; Rose Rahmidani; Efni Cerya (Universitas Negeri Padang, 2018)
This study aims to examined the effect of brand (1) advertising television and packaging design (2) the advertising on television and (3) the design packaging to make the decision to purchase biore’s facial wash toward college students in Universitas Negeri Padang. This type of the research is descriptive causative,the purpose of this research is to describe and also analyze the relationships between one variable and others on to show how can these variables affect other variables. The population of this research are colleges students in Universitas Negeri Padang who has been whatched the advertisement in television and also used the Biore;s facial wash. The sampling technique used was purposive sampling with 100 respondents. The techniques use to analyze this research was multiple regression analysis using the SPSS version 20 program. The results of this research shows that : (1) advertising television and design packaging have a significant effet on purchasing decision, (2) the advertisement in television give significant effect on purchases, (3) packaging design has a significant effect on purchasing decisions.Keywords: Television Advertising, Packaging Design, Purchasing Decision